Promosi Produk Penghimpun Dana Bank Mini Syariah (BMS) Terhadap Minat Menabung Nasabah Di Bank Mini Syariah Mardhotillah Angkola Barat - Purnama Hidayah Harahap; Mita Dwi Priyatni (Jurnal Abdi Mas Adzkia, 2021)
AbstractIslamic finance is a financial institution whose operations are based on Islamic principles. The application of Islamic principles is what distinguishes Islamic financial institutions from general (conventional) financial institutions. The community certainly has significant goals both in terms of achieving goals and realizing the use of Islamic financial services based on the Al-Quran and As-Sunnah. To achieve the goals that have been proclaimed, it is necessary to take action. The action in this case is to invite the people of the Sitinjak village, West Angkola District to save in a mini sharia bank. Therefore, in this journal paper, the researcher aims to increase the insight and knowledge of students and the public about Islamic banking, invite students and the public to join in using Bank i Syariah products and to familiarize students and the public with saving at Islamic banks. This study involved several informants including students, the community and the leadership of the Mini Syariah Bank Pondok Pesantren Mardhotillah by using the interview method. The results obtained include the number of enthusiastic students of the Mardhotillah Islamic boarding school who are enthusiastic about joining the Mini Syariah Bank. There are obstacles related to people's concerns who think that this Mini Syariah Bank is an unclear bank, and the Bank can later cause disappointment